2019
DOI: 10.1155/2019/7932967
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Frequency Response Analysis as a Tool for Identification of Adsorption Kinetics: Case Study—Pore‐Surface Diffusion Control

Abstract: In the present paper, the Nonlinear Frequency Response (NFR) analysis is applied for theoretical study of kinetics of adsorption governed by pore-surface diffusion. The concept of higher-order frequency response functions (FRFs) is used. Based on a nonlinear mathematical model for adsorption of pure gas and spherical adsorbent particles, the theoretical first- and second-order FRFs, which relate the adsorbate concentration in the particle to the surrounding pressure (F1(ω) and F2(ω,ω)), have been derived. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In their later theoretical study of adsorption governed by parallel macropore and micropore diffusion, they found the second-order FRFs exhibit bimodal characteristics that reflect the dynamics of the parallel macropore and micropore diffusion processes. In the combination of second-order FRFs, NFR offers the potential to estimate the values of the macropore and micropore diffusion coefficients, both of practical importance [102]. This suggests the potential of NFR to tackle some of the difficulties of interpreting FR data, while allowing for the simultaneous determination of multiple dynamic rates with shorter experimental times, although the complexity of this analysis is significantly increased.…”
Section: Status and Outlookmentioning
confidence: 99%
“…In their later theoretical study of adsorption governed by parallel macropore and micropore diffusion, they found the second-order FRFs exhibit bimodal characteristics that reflect the dynamics of the parallel macropore and micropore diffusion processes. In the combination of second-order FRFs, NFR offers the potential to estimate the values of the macropore and micropore diffusion coefficients, both of practical importance [102]. This suggests the potential of NFR to tackle some of the difficulties of interpreting FR data, while allowing for the simultaneous determination of multiple dynamic rates with shorter experimental times, although the complexity of this analysis is significantly increased.…”
Section: Status and Outlookmentioning
confidence: 99%
“…Danica et al applied the high-order frequency response function obtained by nonlinear frequency response analysis to pore diffusion analysis [26]. They successfully applied the pioneering research of the frequency response analysis performed by Petkovska et al [27] to separately estimate the pore and surface diffusion coefficients.…”
Section: Introductionmentioning
confidence: 99%